Clinico-pathological study of benign soft tissue tumors: a study from tertiary teaching hospital - Dr Deepak MB; Dr Suchitha S; Dr Manjunath GV; Dr Ira Bharadwaj (Tropical Journal of Pathology and Microbiology)
Background: Aim of the study was to analyze the histopathological findings in various benign soft tissue tumors and to study its frequency distribution in relation to age, gender and anatomical site. Material and Method: Total of 250 cases of soft tissue lesions were analyzed retrospectively and prospectively in a period 2.5 years during June 2009 to Dec 2011. In addition to routine Haematoxylin and Eosin stained sections of all the specimens, special stains with immunohistochemical markers were done wherever necessary. Age and sex incidence, site of lesion, clinical features, gross and microscopic appearance were carefully studied. Result: Of 250 lesions analyzed, 213 (185.2%) were benign soft tissue tumors. Overall a male predominance was seen with 57.4% in males. Majority of the benign tumors occurred in third decade (21%). The most common site of occurrence was head and neck (38%). On gross examination 160(75%) cases measured less than 5cms. Lipoma was the most common benign soft tissue tumor (68 cases, 31.9%) followed by capillary hemangioma (28 cases, 13.1%). Conclusion: The large majority of soft tissue tumors are benign with a very high cure rate after surgical excision. Aggressive benign myxoid soft tissue tumors require wide surgical excision and close follow up. The diagnosis and management of benign soft tissue tumors require a team perspective consisting of clinical, radiological and pathological correlation.